EVALUATING ON-FARM WATER MANAGEMENT IN SMALL-SCALE IRRIGATION SCHEMES IN SOUTHERN ETHIOPIA - Tesfaye H. (Russian Journal of Agricultural and Socio-Economic Sciences)
Ethiopia's agricultural sector is predominantly dependent on rain-fed farming, and irrigation systems are becoming increasingly essential for enhancing productivity and ensuring food security. This study assesses on-farm water management practices within small-scale irrigation schemes in southern Ethiopia, focusing on two irrigation schemes, Wosha and Werka, located in the Wondo Genet District Sidama Region. The physical characteristics of the soil, crop water and irrigation requirements, irrigation scheduling, and application efficiency were evaluated. The findings revealed that Werka exhibited better soil water-holding capacity and higher application efficiency (59%) than Wosha (48.2%). Sugarcane and chat were the dominant crops in both schemes, with irrigation scheduling showing gaps between farmer practices and optimal water intervals, particularly in Wosha. Overall, Werka's irrigation system demonstrated a better performance, highlighting the need for improvements in Wosha’s irrigation management practices. Farmers in both schemes, especially in Wosha, should adopt scientifically calculated irrigation intervals to reduce water wastage and enhance crop yield. Strengthening technical proficiency in water management and providing training on modern irrigation techniques are essential for farmers to optimize water use.